Evolución del somatotipo de jugadores cubanos de voleibol en el periodo 1970-2012 - Carvajal Veitia, W.; Serviat Hung, N. (Archivos de medicina del deporte, 2015)
Objective: To determine the size and direction of changes in anthropometric characteristics of Cuban volleyball players in the period 1970-2012. Material and method: Data on 560 high-standard volleyball players measured between 1967 and 2010 were collated to describe the evolution of body size and shape (somatotype) over the last 40 years. Where only summary statistics like arithmetical mean and standard deviation were presented, Monte Carlo simulation was used to generate pseudo-data. Individual data were available for 480 players. Trained and qualifi ed anthropometrics performed the measurements under standardized experimental conditions and in accordance with the procedures described by the International Biological Programme. These measurements included height, weight, breadths (biepycondylar femur and biepycondyar humerus), girths (arm fl exed and calf ) and skinfold thickness (triceps, subscapular, supraespinal and medial calf ). Results: The rates of increase in stature were 0.18 and 0.22 cm. per year) for male and female respectively. The increase in stature (>1.0 cm per decade) was superior to the secular increase. Since 2010-2012, players have been less endomorphic (-0.01 and -0, 02 units per decade) and less mesomorphic (-0.01 and -0.03 units per year), but much more mesomorphic (0.018 y 0.02 units per year) than before for male and female respectively. Conclusions: The somatotype of Cuban volleyball players has changed in the last ones 40 years toward a more linear and optimal figure, also there has been a secular decline in the endomorphy and mesomorphy. The observed changes may be a consequence of population secular trend or sport morphological adaptation.